Insomnia Symptoms and Their Association with Anxiety and Poor Sleep Hygiene Practices Among Ethiopian University Students - Manzar, Md Dilshad (Nat Sci Sleep, 2020)
OBJECTIVE: There is a paucity of research evidence available regarding the impact of anxiety and sleep hygiene on insomnia and related sleep complaints among collegiate students in lower-income countries. The purpose of this study was to investigate if insomnia and insomnia-related sleep complaints are associated with anxiety, age, and sleep hygiene practices among a sample of university students in Ethiopia. DESIGN, MEASURES, SETTING, AND PARTICIPANTS: The participants were young adults (n=525; mean age 21.5 ± 3.0 years; mean BMI of 20.7 ± 2.7kg/m(2)). Young collegiate adults at Mizan-Tepi University in southwestern Ethiopia were randomly selected to participate in this cross-sectional study. The measures included the Leeds Sleep Evaluation Questionnaire-Mizan (LSEQ-M), the Generalized Anxiety Disorder–7 Scale (GAD-7), and the Sleep Hygiene Index (SHI). Descriptive statistics, binary logistic regression, and multiple linear regressions were used. RESULTS: Insomnia was associated with young age group (≤25 years) (odds ratio (OR) = 2.20, 95% confidence interval (CI) 1.04–4.66), higher GAD-7 (anxiety) (OR = 1.05, 95% CI 1.0–1.10) and SHI (poor sleep hygiene) (OR = 1.15, 95% CI 1.05–1.26) scores. All four insomnia-related sleep complaints were associated with increasing GAD-7 scores, as well as higher SHI scores (p<0.001). CONCLUSION: Insomnia was associated with younger age group (≤25 years), higher anxiety level, and poor sleep hygiene. Four major sleep complaints in insomnia, ie, sleep onset problems, poor sleep quality, awakening problems, and daytime disturbances, were all associated with higher anxiety levels and poor sleep hygiene.